PENGARUH MIND MAPPING DENGAN MODEL PEMBELAJARAN TGT TERHADAP HASIL BELAJAR PADA MATA KULIAH ANATOMI FISIOLOGI HEWAN DI TADRIS IPA UIMSYA - ferdiana, ferdiana; Riris Idiawati, Riris Idiawati; Anis Wildatus, Anis Wildatus (Natural Science Education Research, 2025)
Education has an important role in shaping individuals who are smart, skilled and moral. However, the quality of education in Indonesia still faces various challenges, especially in terms of learning effectiveness and curriculum relevance. Problems found in the environment of Tadris IPA UIMSYA students, especially in learning the Anatomy of Animal Physiology course, include the busy activities of boarding schools, limited time and access to information, and low student motivation to learn. This has an impact on learning outcomes that are less than optimal. Therefore, innovative solutions are needed in learning. One of the proposed solutions is to combine the mind mapping method as a learning medium combined with the TGT (Teams Games Tournament) cooperative learning model, this combination is believed to increase student understanding and activeness in learning. The research method used is quantitative by using experimental method. The results proved that the learning intervention had a significant positive impact on improving student learning outcomes.